منهج أبي الحسن العامري في مقارنة الأديان: دراسة تحليلية - حتقه، هناء إبراهيم أمين (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
The aim of this research is to study the methodology of Abi Al-Hassan Al-'Amiri in comparative religion. To achieve this objective appropriate research methods were utilized. The descriptive method was used to identify the surrounding environment which had an impact on Al-'Amiri's scholary output, by high-lighting the political, economic and social aspects at that time and the role of the scholar and intellectual renaissance in that era. The movement of translated books at that time brought new knowledge to the Muslim scientist. The researcher focused on the overall impact of non-Muslims on the Muslim community. The descriptive method was also used to define the meaning of science and the scholarly divisions of Al-'Amiri, and the scholars from his school. The analytical method was also used to analyze the preference of religious sciences over rational science from his book Al-I'lam bi-manaqib al-Islam, and point out the method of work and science. The study also examined the historical, rational and religious argument, and the methodological basis used in his book. Analyze the methodology of preference in comparative religion that Al-'Amiri used in the book of Manaqeb, and the objectivity of Al-'Amiri in comparative religion. Also the researcher compared Al-'Amiri objectivity with modern rational scholar. The study concluded with a series of results, the most important of which is that Al-'Amiri in the comparison of religions wanted to show the virtue of the Islamic religion over other religion through two main points. First, the superiority of the divine sciences as a science. And second the preference for Islamic religion as a religion with doctrines, worship and worldly practices.